Adenomyomectomy, curettage, and then uterine artery pseudoaneurysm occupying the entire uterine cavity. Issue 5 (4th April 2013) - Matsubara, Shigeki; Usui, Rie; Sato, Tomomi; Kuwata, Tomoyuki; Ohkuchi, Akihide; Nakata, Manabu
Abstract Uterine artery pseudoaneurysm can occur after cesarean section or traumatic delivery, usually manifesting as postpartum hemorrhage. Pregnant women after adenomyomectomy sometimes suffer some adverse events, among which uterine rupture has been widely acknowledged. We describe a post‐abortive woman who had uterine artery pseudoaneurysm occupying the entire uterine cavity. She underwent adenomyomectomy and became pregnant. She experienced a missed abortion and underwent evacuation and curettage, which caused bleeding. Several days later, ultrasound revealed an intrauterine mass with marked blood flow. Angiography revealed the un‐ruptured left uterine artery pseudoaneurysm, with arterial embolization stopping the flow within the pseudoaneurysm. Adenomyomectomy with subsequent curettage was considered to have caused the pseudoaneurysm. We must be cautious that pseudoaneurysm may occur in post‐abortive women after adenomyomectomy.